Vladyslav Volodymyrovych Povorozniuk - "ORTHOPAEDICS, TRAUMATOLOGY AND PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On June 12, 2021, Vladyslav Volodymyrovych Povoroznyuk, the scientific director of the Department of Clinical Physiology and Pathology of the Musculoskeletal System of the State Institution “Institute of Gerontology named after DF Chebotaryov NAMS of Ukraine ", President of the Ukrainian Association of Osteoporosis and the Ukrainian Association of Menopause, Andropause and Musculoskeletal Diseases, President of the Ukrainian Division of EVIDAS, Member of the Board of the International Osteoporosis Association (IOF), Deputy Chairman of the Gerontologist Of Ukraine, Vice President of the Ukrainian Association of Rheumatologists, Member of the Board of the Ukrainian Association of Orthopedists-Traumatologists, Member of the Public Council of the Ukrainian Federation of Public Organizations for Civil Society Health Promotion, Honorary Member of the Association of Implantologists of Ukraine, Member of International Associations ACR, ASB EFORT, EMAS, EULAR, ISCD, ISSAM, OARSI, SICOT, director of the Ukrainian Scientific and Medical Center for Osteoporosis.